Work capacity, sociodemographic and work characteristics of nurses at a university hospital Capacidad de trabajo, características sociodemográficas y laborales de las enfermeras de un hospital universitario Capacidade para o trabalho, características sociodemográficas e laborais de enfermeiros de um hospital universitário - Eunice Fabiani Hilleshein; Liana Lautert (Universidade de São Paulo, 2012)
This cross-sectional study evaluated the work capacity of 195 nurses at a university hospital, from a calculation of sample size with a Confidence Interval (CI) of 95%. The data was collected by means of the Work Capacity Index (WCI) instrument and analyzed by statistical analysis. 94.5% of the sample was made up of women; the average age was of 42.6 years (sd=8.5); 66.5% had partners and 76.7% were educated to post-graduate level. 36.0% worked the night shift; 28.4% the morning shift and 20.8% the afternoon shift. The average score given to work capacity was Good (41.8 points) and there was a significant correlation with pay (p-value<0.05), satisfaction with workplace (p-value=0.001) and feeling valued by the institution (p-value=0.003). The group which carried out family activities showed higher scores in the WCI compared to those who did not (p-value=0.009). The nurses presented differing sociodemographic and work aspects, with a high capacity for work. El estudio transversal evaluó la capacidad de 195 enfermeras que trabajan en un hospital universitario del cálculo de la muestra es del 95%. Los datos fueron recogidos por el Índice de Instrumento Capacidad para el Trabajo y analizados por estadísticas y análisis y, 94,5% de la muestra eran mujeres, edad media de 42,6 años (SD=8,5), el 66,5% con los compañeros y 76,7% tiene un post-grado. El puntaje promedio de la capacidad de trabajo fue buena (41,8 puntos) y una correlación significativa con la remuneración (p<0,05), satisfacción con el trabajo (p=0,001), la recuperación por la institución (p=0,003). Y el grupo que lleva a cabo programas en las familias presentan puntuaciones superiores en las ICT a los que no las realizan (p=0,009). Las enfermeras tenían diferentes aspectos de los cambios demográficos y laborales, con alta capacidad para el trabajo. O estudo transversal avaliou a capacidade para o trabalho de 195 enfermeiros de um hospital universitário, a partir do cálculo amostral com IC de 95%. Os dados foram coletados por meio do instrumento Índice de Capacidade para o Trabalho (ICT) e analisados por estatística analítica, sendo que 94,5% da amostra era composta por mulheres com idade média de 42,6 anos (dp=8,5), 66,5% com companheiros e 76,7% tinham pós-graduação. Quanto ao turno de trabalho, 36% atuava à noite; 28,4% pela manhã e 20,8% à tarde. O escore médio de capacidade para o trabalho foi Bom (41,8 pontos) e houve correlação significativa com a remuneração (p-valor<0,05), satisfação com o local de trabalho (p-valor=0,001), valorização por parte da instituição (p-valor=0,003). E o grupo que realiza programas em família apresentou escores superiores no ICT aos daqueles que não as realizam (p-valor=0,009). Os enfermeiros apresentaram aspectos sociodemográficos e laborais diferenciados, com elevada capacidade para o trabalho.